2015
DOI: 10.1007/s00226-015-0757-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent research and development advances of wood science and technology in China: impacts of funding support from National Natural Science Foundation of China

Abstract: In the past decades, the field of wood science and technology (WST) in the world has experienced significant changes in response to changes in resources, environments, technologies, and other emerging issues. WST in China is becoming a strong scientific discipline and has had an obvious impact on the global WST research and development (R&D) activities. In this article, a comprehensive review of the recent WST R&D advances in China is presented. Among various contributing factors, the National Natural Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Traditional flame-retardant processing techniques involve soaking with flame retardants and applying organic fire-proof coatings or inorganic coatings to the wood surface. Inorganic coatings such as TiO 2 , SiO 2 , ZnO, FeOOH, and Al­(OH) 3 are nontoxic and not as easily run out as traditional organic retardants. They not only provide stiffness, hydrophobicity, UV resistance, and antimicrobial properties to wood but also reduce its flammability and smoke production. Saka et al, for example, reported that Al­(OH) 3 - or SiO 2 -based polynary inorganic oxides are very successful in endowing wood materials with flame retardancy .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional flame-retardant processing techniques involve soaking with flame retardants and applying organic fire-proof coatings or inorganic coatings to the wood surface. Inorganic coatings such as TiO 2 , SiO 2 , ZnO, FeOOH, and Al­(OH) 3 are nontoxic and not as easily run out as traditional organic retardants. They not only provide stiffness, hydrophobicity, UV resistance, and antimicrobial properties to wood but also reduce its flammability and smoke production. Saka et al, for example, reported that Al­(OH) 3 - or SiO 2 -based polynary inorganic oxides are very successful in endowing wood materials with flame retardancy .…”
Section: Introductionmentioning
confidence: 99%
“…Wood is an oldest biomass material, which has been exploited and utilized by humans for thousands of years, because of its renewable characteristic, low weight‐to‐strength ratio, beautiful texture, high mechanical strength, and low thermal conductivity . Based on the 3D porous architecture consisting of cellulose, hemicellulose, and lignin of natural wood, many approaches on the modification and functionalization of wood have been presented to improve its quality and raise its added value . For example, Li and co‐workers proposed a new kind of wood‐based nanocomposites with satisfactory durability and high specific strength via a vacuum impregnation of organic–inorganic polymer into wood porous structure .…”
Section: Introductionmentioning
confidence: 99%
“…At present, research of flame retardants for bamboo is mainly based on that of wood fire retardants. The application of phosphorus-nitrogen-boron synergistic flame retardants in the field of wood has matured into a relatively stable phase (Branca and di Blasi 2007;Chou et al 2010;Zhao and Yu 2016). This provides beneficial theoretical support for the study of bamboo flame retardants.…”
Section: Introductionmentioning
confidence: 97%